Towards an ecological account of media choice: a case study on pluralistic reasoning while choosing email. (29th May 2013) - Jung, Yusun; Lyytinen, Kalle
Abstract The discourse around media choice has generated a diverse array of media choice factors originating from both the media‐based and social interaction‐based approaches. The multitude of these factors hints at the adaptive nature of media choice. Alas, how a user engages with such factors and adaptively carries out media choice has remained understudied. We undertake a field study to explore the role of a plurality of choice factors and their interactions in shaping media choice processes and outcomes. In particular, we focus on how a user identifies relationships among plural choice factors while he or she works on his or her particular choice resulting in a similar outcome – email – given a large number of alternatives. Drawing upon a theory of affordances, we propose a systemic way of narrating the dynamics of media choice as a multi‐dimensional process where a user explores her or his surroundings – a niche – as to establish media affordances that will then help her or him achieve a communication goal. We identify five relational patterns of interactions among specific choice factors: reciprocity, emergence, complementarity, re‐exploration and actualisation. These patterns are shown to be emergent and highly interdependent. We conclude by reviewing future research avenues to formulate richer 'ecological' accounts of media choice.